Philosophy of Logic and Mathematics Proceedings of the 41st International Ludwig Wittgenstein Symposium - Mras, Gabriele M.; Weingartner, Paul; Ritter, Bernhard (Publications of the Austrian Ludwig Wittgenstein Society - New Series ;, 2019)
This volume presents different conceptions of logic and mathematics and discuss their philosophical foundations and consequences. This concerns first of all topics of Wittgenstein's ideas on logic and mathematics; questions about the structural complexity of propositions; the more recent debate about Neo-Logicism and Neo-Fregeanism; the comparison and translatability of different logics; the foundations of mathematics: intuitionism, mathematical realism, and formalism